Le port de Montréal à la veille de l’ouverture de la nouvelle voie navigable du Saint-Laurent - Camu, Pierre (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1958)
A few months before the opening of the new St. Lawrence Seaway, the author reappraises the effects of the Project on the Port of Montréal. Analysing the conclusions and recommendations of three studies published in 1957 and 1958, the Report of the ToIIs Committee of the St. Lawrence Seaway, the Report of the Royal Commission on Coastal Trade, and the report published by the Faculty of Commerce of McGill University, The Impact of the St. Lawrence Seaway on the Montréal Area, one comes to the conclusion that the Port of Montréal will remain a grain transhipment centre, but will lose a good part of its general cargo trade to Great Lakes ports. The loss of general cargo tonnage is estimated at 650,000 tons. In conclusion, several factors that may contribute to keep Montréal the leading oceanic port on the Seaway are stressed : 1. the imponderables ; 2. the Lachine rapids that are reduced in size by the new canal, but do not disappear; 3. competition between different types of vessels ; and, 4. traffic congestion in the waterway.